Sekolah Sebagai Sarana Menanamkan Nilai Budaya dan Karakter Bangsa - Ahmad Aspiani; Miranda Miranda; Reza Maulana Dalimunte (JOURNAL SAINS STUDENT RESEARCH, 2025)
In the era of globalization and digitalization, challenges to national identity are increasingly complex due to shifting values and cultural influences. This study aims to explore the strategic role of schools in strengthening character education through school culture, integration of local wisdom, and the implementation of the Merdeka Curriculum. Using a descriptive qualitative approach and thematic analysis techniques, the study reveals that schools serve as key agents of cultural transformation and guardians of national values. The findings indicate that character development can be effectively achieved through synergy between formal education, local cultural practices, school leadership, teacher role modeling, and collaboration among schools, families, and communities. A consistent school culture, context-based learning rooted in Pancasila values, and extracurricular activities highlighting local culture have been proven to foster students’ tolerance, responsibility, and patriotism. These findings emphasize the importance of holistic and contextual approaches in developing student character grounded in the Indonesian national identity.